PENGARUH IKLAN, BRAND IMAGE DAN LABELISASI HALAL TERHADAP MINAT BELI SANTRIWATI PADA PRODUK KECANTIKAN KOSMETIK WARDAH MENURUT PRESFPEKTIF EKONOMI ISLAM DI ASRAMA I PONDOK PESANTREN NGALAH PURWOSARI PASURUAN - Abdillah Mundir; Muhammad Nizar; Ajeng Rima Mustaqimah; Faujiah, Ani (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2021)
This study aims to determine the effect of advertising, brand image and halal label on interest in buying cosmetics through a survey of Wardah cosmetics users in Dormitory I Pondok Pesantren Ngalah Purwosari Pasuruan. This research is a quantitative research. The sample in this study were 66 respondents who were taken from female students who became cosmetic users. Data collection techniques in the field using questionnaires and interviews at random and unstructured. Based on the research data, the results obtained for each variable partially with a significance level less than 5%, where advertising (X1) with a significance level of 0.084 < 0.005, and brand image (X2) with a significance level of 0.277 < 0.005, and halal labeling ( X3) with a significance of 0.473 <0.005 has fulfilled the requirements as a supporting variable for buying interest. This means that the three variables studied have an influence on the buying interest of Wardah cosmetic users. Furthermore, by using the f test, it is known that all independent variables simultaneously have a significant effect, where 0.036 <0.05. And finally the calculation of the coefficient of determination shows that all dependent variables, namely advertising (X1) brand image (X2), halal label (X3), can explain the buying interest variable (Y) by 8.6%, the remaining 99.914% is influenced by other variables. which were not investigated in this study. Keywords: Advertising, Brand Image, Halal Labeling DAFTAR PUSTAKA Darmdi Durianto, Invasi Pasar Dengan Iklan yang Efektif, PT. SUN, Jakarta, h.1 Kotler, Bramantya, Yan Bayu,. 2016. Pengaruh Brand Image Terhadap Minat Beli Produk Kosmetika Wardah Di Kota Pagar Alam. Jurnal Ekonomia,Vol.10,No.1Februari.2020 Kotler, K. 2009, Manajemen Pemasaran 1, Jakarta: Erlangga. Matsani Zuhaenif, 2018, Ekonomi Syariah dan Peran Muslimah melalui https://www.kompasiana.com/zoelzul/54feceeaa3331835a50f824/menunggu-peranmuslimahdalam-pngembangan-ekonomi-syarah-indonesia. Diakses pada 27 Agustus. Natalia, Sheyrent. 2013, Analisa Prediksi Atau Penilai Efektivitas Penggunaan Selebritas Sebagai Brand Endorser Untuk Membangun Brand Image (Studi Kasus Iklan The Face Shop), Jurnal, Manajemen Pemasaran Petra Vol. 1, No. 1. Negoro, Prakoso. 2017, Analisis Strategi Pemasaran Produk Kosmetik Wardah Dengan Pendekatan SWOT-AHP, Jurnal, Sain Dan Seni ITS Vol. 6, No. 1. Nizar, Muhammad. 2018, Pendekatan Komprehensif E-Commerce Prefpektif Syariah, Jurnal, Universitas Yudharta. Respati, Dian Widya, Pengaruh Brand Ambassador, Brand Image dan Kualitas Produk Terhadap Minat Beli Produk Lipstik Wardah. Supranto, J. 2011, Pengukuran Tingkat Kepuasan Pelanggan Untuk Menaikkan Pangsa Pasar, Jakarta: Cetakan Keempat, PT Rinela Cipta. Yuswohady, 2015, Mareting To The Middle Class Muslim, Jakarta: Gramedia Pustaka Utama.